Tourism development in local communities: as a community development approach - Aref, Fariborz; Gill, Sarjit S.; Aref, Farshid (Marsland Press, 2010)
This article illustrates the role of local communities for tourism development. This study also attempts to highlight the role of tourism local development. This article looks at how local communities can develop tourism in local area. The concepts of community and community development have been important for local tourism development. The implication of this study arises from the fact that there has been little research carried out on interaction between communities and local tourism. Theoretically, the findings of this study enrich the knowledge concerning local tourism industry.